2017
DOI: 10.1111/pbi.12688
|View full text |Cite
|
Sign up to set email alerts
|

Drought coping strategies in cotton: increased crop per drop

Abstract: SummaryThe growth and yield of many crops, including cotton, are affected by water deficit. Cotton has evolved drought specific as well as general morpho‐physiological, biochemical and molecular responses to drought stress, which are discussed in this review. The key physiological responses against drought stress in cotton, including stomata closing, root development, cellular adaptations, photosynthesis, abscisic acid (ABA) and jasmonic acid (JA) production and reactive oxygen species (ROS) scavenging, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
154
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(160 citation statements)
references
References 118 publications
(108 reference statements)
5
154
0
1
Order By: Relevance
“…Asterisk represents significant difference in mz/rt peak between sensitive (G1) and tolerant (G2) varieties under the drought condition at a specific time point of samplingPereira, 2016;Cielniak, Filek, & Cielniak, 2006;J. Li et al, 2017;Luo, Zhang, & Zhang, 2016;Ullah, Sun, Yang, & Zhang, 2017;Zhou et al, 2017). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Asterisk represents significant difference in mz/rt peak between sensitive (G1) and tolerant (G2) varieties under the drought condition at a specific time point of samplingPereira, 2016;Cielniak, Filek, & Cielniak, 2006;J. Li et al, 2017;Luo, Zhang, & Zhang, 2016;Ullah, Sun, Yang, & Zhang, 2017;Zhou et al, 2017). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
supporting
confidence: 90%
“…However, the sensitive variety showed greater F v / F m reduction than the tolerant variety. Some other studies also demonstrated a significant reduction of photosynthetic capacity and chlorophyll content due to stress condition (Basu, Ramegowda, Kumar, & Pereira, ; Cielniak, Filek, & Cielniak, ; J. Li et al, ; Luo, Zhang, & Zhang, ; Ullah, Sun, Yang, & Zhang, ; Zhou et al, ). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
Section: Discussionmentioning
confidence: 89%
“…Under stresses, stomata closure and a low transpiration rate helps plants to withstand harsh environmental conditions. Waxy leaf cuticles are another adaptation to reduce the transpiration rate (Ullah et al 2017), while our results show that the number of stomata may be higher and/or opened in TRV:GhWRKY6-like plants which reveal its positive role in reducing the transpiration rate.…”
Section: Discussionmentioning
confidence: 58%
“…The sucrose nonfermenting 1-related protein kinase 2 (SnRK2s) are autoactivated when they dissociate from PP2Cs. Activated SnRK2s phosphorylates downstream targets and regulates many stress-related genes to enhance osmotic stress tolerance (Ullah et al 2017). We hypothesized that overexpressing GhWRKY6-like enhanced osmotic stress RT-PCR analysis confirmed that GhWRKY6-like has been silenced in TRV:GhWRKY6-like-cotton-seedlings successfully through VIGS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation